Textural evolution of perovskite in the Afrikanda alkaline-ultramafic complex, Kola Peninsula, Russia - Potter, NJ; Ferguson, MRM; Vadim Kamenetsky; Chakhmouradian, AR; Sharygin, VV; Thompson, JM; Karsten Goemann (2018)
Perovskite is a common accessory mineral in a variety of mafic and ultramafic rocks, but perovskite deposits are rare and studies of perovskite ore deposits are correspondingly scarce. Perovskite is a key rock-forming mineral and reaches exceptionally high concentrations in olivinites, diverse clinopyroxenites and silicocarbonatites in the Afrikanda alkaline–ultramafic complex (Kola Peninsula, NW Russia). Across these lithologies, we classify perovskite into three types (T1–T3) based on crystal morphology, inclusion abundance, composition, and zonation. Perovskite in olivinites and some clinopyroxenites is represented by fine-grained, equigranular, monomineralic clusters and networks (T1). In contrast, perovskite in other clinopyroxenites and some silicocarbonatites has fine- to coarse-grained interlocked (T2) and massive (T3) textures. Electron backscatter diffraction reveals that some T1 and T2 perovskite grains in the olivinites and clinopyroxenites are composed of multiple subgrains and may represent stages of crystal rotation, coalescence and amalgamation. We propose that in the olivinites and clinopyroxenites, these processes result in the transformation of clusters and networks of fine-grained perovskite crystals (T1) to mosaics of more coarse-grained (T2) and massive perovskite (T3). This interpretation suggests that sub-solidus processes can lead to the development of coarse-grained and massive perovskite. A combination of characteristic features identified in the Afrikanda perovskite (equigranular crystal mosaics, interlocked irregular-shaped grains, and massive zones) is observed in other oxide ore deposits, particularly in layered intrusions of chromitites and intrusion-hosted magnetite deposits and suggests that the same amalgamation processes may be responsible for some of the coarse-grained and massive textures observed in oxide deposits worldwide.